(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Although meditation is an effective tool for increasing employee productivity, well being, and job satisfaction, research on the effects of meditation on other corporate factors such as presenteeism and emotional intelligence is limited. The study looked into the effects of meditation on awareness, emotional understanding, job satisfaction, and presenteeism in female corporate employees. The present study is focused on corporate female employees to find out the barriers to meditation. Researcher said that many do not believe in meditation would help in anyways reducing stress inspite of proven studies. Few have no time to spend for meditation though they don’t mind trying. Few have tried meditation and was relaxing but still couldn’t continue coz of stress or work load. Understanding the practical challenges of meditation and helping patients and clients overcome those challenges will benefit from a psychometrically valid measure of meditation barriers. Finally, measuring meditation barriers is useful in both research and practice because it aids in the identification of personal and contextual variables related to meditation barriers.